Clinical and laboratory data of primary hemophagocytic lymphohistiocytosis: A retrospective review of the Turkish Histiocyte Study Group - (:unkn) unknown (My University, 2010)
AMAÇ: Primer hemofagositik lenfohistiositoz tanısı ile Türkiye’deki farklı merkezlerde takip edilen hastaların klinik ve laboratuar değerlerini değerlendirmektir. YÖNTEMLER: Hasta verilerinin değerlendirilmesi için Türk Histiosit Çalışma Grubu tarafından düzenlenmiş 3 sayfalık soru formu kullanıldı. BULGULAR: Olguların tanı sırasındaki yaşları 0.6 ile 78 ay arasında idi (median±SD, 16.5±26.1). Cinsiyet dağılımı eşite yakındı (K/E=10/12). Anne-baba akrabalığı ve kardeş ölüm öyküsü oranları sırası ile %100 ve %81.1 idi. Ensık görülen klinik bulgular hepatomegali (%100), ateş (%95), labaratuvar bulguları ise anemi (%100), hiperferritinemi (%100) ve trombositopeniydi (%90.9). Ölen olguların trigliserid ve bilirubin düzeyleri yüksek gibi gözükmekteydi (trigliserid; 394±183 mg/dL, 289±7 mg/dL, total bilirubin; 2.7±6.9 mg/dL, 0.5±1.2 mg/dL) SONUÇ: Ateş, hepatosplenomegali, anemi, hiperferritinemi ve trombositopeni primer HLH'li hastalarda en sık görülen klinik ve labaratuvar bulgulardır. Tanı sırasındaki artmış trigliserid ve bilirubin düzeyleri kötü prognostik belirteç olabilir.

Objective: This study analyzes the clinical and laboratory findings of children with primary hemophagocytic lymphohistiocytosis (HLH) followed in various referral centers of Turkey. Materials and Methods: A simple three-page questionnaire prepared by the Turkish Histiocyte Study Group was used for documentation of patient data. Results: Age at diagnosis varied from 0.6 to 78 months (median±SD, 16.5±26.1). Sex distribution was almost equal (F/M=10/12). The frequencies of parental consanguinity and sibling death in the family history were 100% and 81.1%, respectively. The most common clinical findings were hepatomegaly (100%) and fever (95%). The most common laboratory findings were anemia (100%), hyperferritinemia (100%) and thrombocytopenia (90.9%). Triglyceride and total bilirubin levels in the deceased versus surviving group appear to be high (triglyceride: 394±183 mg/dl, 289±7 mg/dl; total bilirubin: 2.7±6.9 mg/dl, 0.5±1.2 mg/ dl, respectively).Conclusion: We concluded that fever, hepatosplenomegaly, anemia, thrombocytopenia, and hyperferritinemia are the most common clinical and laboratory findings in primary HLH. Increased triglyceride and total bilirubin level at the time of diagnosis might be an indicator of poor prognosis in HLH. (Turk J Hematol 2010; 27: 157-62)
Primer hemofagositik lenfohistiositozisli hastaların klinik ve labarotuvar verileri; Türk Histiosit Çalşşma Grubunun retrospektif derlemesi
Keywords: Hematoloji